2006
DOI: 10.1074/jbc.m606349200
|View full text |Cite
|
Sign up to set email alerts
|

Fission Yeast Homologs of Human Histone H3 Lysine 4 Demethylase Regulate a Common Set of Genes with Diverse Functions

Abstract: Schizosaccharomyces pombe contains two proteins, SWIRM1 and SWIRM2, with close homology to human histone H3 lysine 4 demethylase. Both proteins contain the amino oxidase catalytic domain and a recently described DNA interaction SWIRM domain. Here we describe the biochemical isolation and the functional characterization of SWIRM1 and SWIRM2. Our results indicate that while SWIRM2 is an essential gene, cells lacking SWIRM1 are viable. We found that SWIRM1 and SWIRM2 are stably associated in a multiprotein comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 34 publications
9
32
1
Order By: Relevance
“…The results of the MS analysis are presented in Table S1 in the Supplementary Information and are summarized in Figure 1. In brief, our data confirm the results of Nicolas et al, (2006) [14] and show that the Swm1 complex contains Swm2 and two new PHD domain containing proteins ( S. pombe DB CDS: SPCC4G3.07 and SPAC30D11.08c), hereafter referred to as Swp1 ( Sw m associated P HD1) and Swp2 ( Sw m associated P HD2). Surprisingly, the purified Swm2 complex contained only Swm1 and Swp1, but not Swp2, suggesting that the Swm proteins may exist in more than one complex.…”
Section: Resultssupporting
confidence: 92%
“…The results of the MS analysis are presented in Table S1 in the Supplementary Information and are summarized in Figure 1. In brief, our data confirm the results of Nicolas et al, (2006) [14] and show that the Swm1 complex contains Swm2 and two new PHD domain containing proteins ( S. pombe DB CDS: SPCC4G3.07 and SPAC30D11.08c), hereafter referred to as Swp1 ( Sw m associated P HD1) and Swp2 ( Sw m associated P HD2). Surprisingly, the purified Swm2 complex contained only Swm1 and Swp1, but not Swp2, suggesting that the Swm proteins may exist in more than one complex.…”
Section: Resultssupporting
confidence: 92%
“…These studies have corroborated the notion that LSD1 can act as a H3K9 demethylase associated with heterochromatin boundaries and euchromatic promoters (Nicolas et al 2006;Lan et al 2007c) or as a H3K4 demethylase (Rudolph et al 2007). Thus, in S. pombe the LSD1 ortholog SWIRM1/2 (also referred to as spLsd1/2) has been demonstrated to demethylate H3K9 and depletion of SWIRM1/2 induces heterochromatin spreading beyond normal heterochromatin regions (Lan et al 2007c).…”
Section: The Amine Oxidase Lsd1 (Kdm1)supporting
confidence: 66%
“…Studies performed in Schizosacchaomyces pombe and Drosophilia melanogaster have implicated LSD1 orthologs in the organization of higher-order structure of chromatin (Nicolas et al 2006;Lan et al 2007c;Rudolph et al 2007). These studies have corroborated the notion that LSD1 can act as a H3K9 demethylase associated with heterochromatin boundaries and euchromatic promoters (Nicolas et al 2006;Lan et al 2007c) or as a H3K4 demethylase (Rudolph et al 2007).…”
Section: The Amine Oxidase Lsd1 (Kdm1)mentioning
confidence: 99%
“…Extensive biochemical testing of both native and recombinant SAPHIRE complexes has not revealed appreciable activity. This is consistent with the work of others on these S. pombe orthologs, showing no observed activity in vitro (31). Therefore, we focused on the biological and genomic impact of removing the conserved catalytic residue of these enzymes, as described below.…”
Section: Saphire Binds Nucleosomessupporting
confidence: 65%
“…Our in vivo work also provides several lines of evidence that SAPHIRE promotes gene activation. While we were preparing this paper for submission, others purified a complex of largely the same composition, localized the complex to promoters, and demonstrated that transcription is reduced at three selected targets in saf110⌬ mutants (31). However, our work is unique in its (i) evidence for nucleosome binding, (ii) examination of knockouts of all four complex members, (iii) preparation and analysis of catalytically impaired mutants, (iv) observation of occupancy of the complex at heterochromatin regions, (v) genome-wide analysis of the impact of both saf110⌬ and catalytic mutants on transcription, (vi) observation of changes in histone methylation that occur in catalytic mutant strains at occupied genes, (vii) observation of dynamic relocalization of SAPHIRE during gene activation, and (viii) demonstration of a large shift in the euchromatin-heterochromatin boundary at chromosome 1 in catalytic mutants, suggesting a novel role in boundary formation.…”
Section: Discussionmentioning
confidence: 99%